Blind estimation of pseudo-random codes in non-periodic long code direct-sequence spread-spectrum signals - HAOZhi-jin Z; UXiao-wei G; HENLei S; HANYi Z (Tongxin xuebao)
The existence of common peaks in triple correlation functions of different m-sequences is proven based on the detail study of the characteristics of triple correlation functions of m-sequences,the features of common peaks and the direct relationship between common peak coordinates and the primitive polynomials of m-sequences are deduced.An es-timation algorithm of pseudo-random (PN) codes in non-periodic long code direct-sequence spread-spectrum (NPLC-DSSS) signals is proposed based on the above theories.Simulations under additive white Gaussian noise show that the probability of spreading code and scrambling code being both correctly estimated can reach 99% when the signal with a quarter of the cycle length of the long PN code is used only and the signal-to-noise ratio is greater than 4dB.